Influence of high levels of zinc oxide in starter diets on pig performance - Tokach, Lisa M.; Henry, Steven C.; Marstelller, T.A.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials were conducted to determine the influence of high levels of zinc oxide on starter pig performance. Two dietary treatments (110 or 3,110 ppm zinc) were used in each trial. In trial 1, 180 pigs (17 d of age and 10.9 lb) were blocked by weight and allotted to 20 pens for a total of eight or nine pigs/pen and 10 pens/treatment. In trial 2, 168 pigs (21 d of age and 12.8 lb) were blocked by weight and sex and allotted to six pens for a total of 28 pigs/pen and three pens/treatment. Experimental diets were fed for d 0 to 14 after weaning (phase I). All pigs were fed a common diet containing 110 ppm zinc during phase II (d 14 to 25 in trial 1 and d 14 to 29 in trial 2). Adding 3,000 ppm zinc as zinc oxide to the starter diet did not influence starter pig performance in either trial.
Keywords: Swine; Zinc; Starter; Performance